2018
DOI: 10.21608/zjar.2018.47889
|View full text |Cite
|
Sign up to set email alerts
|

BIOSYNTHESIS, OPTIMIZATION AND CHARACTERIZATION OF SILVER NANOPARTICLES BIOSYNTHESIZED BY Bacillus subtilis ssp spizizenii MT5 ISOLATED FROM HEAVY METALS POLLUTED SOIL

Abstract: Nanotechnology and nanoparticles (NPs) researches have attracted a lot of interest in recent decades, and there is growing attention to find more effective ways for their synthesis. The use of biological approach, (using various microorganisms), as bio-nanofactories provides a clean and promising alternative process for the fabrication of silver nanoparticles. This study confirmed the production of silver nanoparticles (AgNPs) by a cost effective, safe and environment-friendly technique using silver nitrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…By using the recent approaches of nanotechnology, the biological synthesis of SeNPs with high efficiency, low-cost and accurate productivity has replaced the traditional physical and chemical procedures ( Wadhwani et al, 2016 ). Biosynthesis of NPs involves the use of uni- and multi-cellular microorganisms including bacteria and fungi ( El-Saadony et al, 2018; El-Saadony et al, 2021a; El-Saadony et al, 2021b; El-Saadony et al, 2021c; El-Saadony et al, 2021d; Reda et al, 2021 ), yeasts ( Moghaddam et al, 2017 , Shamsuzzaman et al, 2017 ), algae ( Azizi et al, 2014 ), and some nonliving viral particles ( Nam et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…By using the recent approaches of nanotechnology, the biological synthesis of SeNPs with high efficiency, low-cost and accurate productivity has replaced the traditional physical and chemical procedures ( Wadhwani et al, 2016 ). Biosynthesis of NPs involves the use of uni- and multi-cellular microorganisms including bacteria and fungi ( El-Saadony et al, 2018; El-Saadony et al, 2021a; El-Saadony et al, 2021b; El-Saadony et al, 2021c; El-Saadony et al, 2021d; Reda et al, 2021 ), yeasts ( Moghaddam et al, 2017 , Shamsuzzaman et al, 2017 ), algae ( Azizi et al, 2014 ), and some nonliving viral particles ( Nam et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 E showed the time dependence of Myco-SNPs using a 1 mM AgNO 3 solution. It revealed that as reaction time increased, the color of the resulting solutions changed and absorption increased, indicating the formation of more Myco-SNPs up until day 5, which demonstrates the stabilization of Myco-SNPs solution [ 66 ]. Day 5 was considered the optimum time for Myco-SNPs production from A. flavipes AUMC 15772.…”
Section: Resultsmentioning
confidence: 99%